Nuclear Spin Relaxation of Longitudinal and Singlet Order in Liquid-CO2 Solutions - Moysiadi, Aliki; Giustiniano, Francesco; Hall, Andrew M. R.; Cartlidge, Topaz A. A.; Brown, Lynda J.; Pileio, Giuseppe (Frontiers in Chemistry, 2021)
Hyperpolarization techniques can enormously enhance the NMR signal thus allowing the exploitation of hyperpolarized substrates for in-vivo MRI applications. The short lifetime of hyperpolarized spin order poses significant limitations in such applications. Spin order storage can be prolonged through the use of long-lived spin states. Additionally, the storage of spin polarization - either in the form of longitudinal or singlet order - can be prolonged in low viscosity solutions. Here, we report the use of low viscosity liquid-CO2 solutions to store nuclear spin polarization in the form of longitudinal and singlet order and for extended periods. Our results demonstrate that this storage time can be considerably sustained in liquid-CO2 solutions in comparison to other low viscosity solvents, opening up the possibility of new, exciting storage experiments in the future.